Storm Castle ORT - Hunt, Rodreick, 2012; Roderick Hunt, 1993; Alex Brychta, 1993 (Oxford university press UK, 1993)
"Storm Castle" by Judith E. French is a historical novel set in medieval times, focusing on themes of loyalty, love, and the complexities of power. The story follows a young protagonist who navigates the dangers of court intrigue and battles while seeking to reclaim their family's honor. Throughout the narrative, characters face moral dilemmas and shifting allegiances, highlighting the harsh realities of life in a feudal society. The backdrop of castle life and warfare adds tension and depth, ultimately leading to a dramatic conclusion that underscores the resilience of the human spirit.
Book Title: Storm Castle Series: Oxford Reading Tree: Stage 9 Genre: Adventure / Fantasy / Science Fiction Word Count: Approx. 1,300 words Illustrator: Alex Brychta Author: Roderick Hunt and Alex Brychta
H3
The children are transported into a virtual reality game called Storm Castle. They must complete a series of challenges inside the castle using problem-solving skills, teamwork, and quick thinking. The story blends adventure and science fiction elements while promoting digital literacy themes.
Keywords: Supplementary reading material